2010
DOI: 10.4137/jcnsd.s6411
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Discharge to Home after Thrombolytic Treatment in Right Hemisphere Infarct Patients

Abstract: BackgroundThe aim of the study was to assess the association between thrombolysis and length of hospital stay after right hemisphere (RH) infarct, and to identify which cognitive functions were predictive of discharge.MethodsThe study group consisted of 75 acute RH patients. Thirty-three patients had thrombolysis. Neuropsychological examinations were performed within 11 days of stroke onset. The cognitive predictors were visual neglect, visual memory, visual search and reasoning and visuoconstructive abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Poor outcome at day 7 (short term) was defined by NIHSS score ≥5 in hospital . We estimated the functional outcome after discharge using the ordinal score on the modified Rankin scale (mRS; range, 0‐6, with higher scores indicating greater disability) at 3, 6, and 12 months (long term) visit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor outcome at day 7 (short term) was defined by NIHSS score ≥5 in hospital . We estimated the functional outcome after discharge using the ordinal score on the modified Rankin scale (mRS; range, 0‐6, with higher scores indicating greater disability) at 3, 6, and 12 months (long term) visit.…”
Section: Methodsmentioning
confidence: 99%
“…in hospital. 21 We estimated the functional outcome after discharge using the ordinal score on the modified Rankin scale (mRS; range, 0-6, with higher scores indicating greater disability) at 3, 6, and 12 months (long term) visit. The mRS score was used as a clinician-reported measure of global disability and assessed by professional neurologists, and functional independence (defined as a score on the mRS of 0-2) represented a good outcome, whereas functional dependence (defined as a score on the mRS of ≥3) represented a poor one.…”
Section: Outcome Definitionsmentioning
confidence: 99%
“…Our finding about thrombolysis not being a statistically significant predictor of instrumental functional outcome (IADL), although it has been shown to be a significant predictor of earlier discharge to home in patients with moderate/severe RH infarct (Ruuskanen et al, 2010), suggests that also in future studies functional outcome should be evaluated taking into account both ADL and IADL outcome. Since our findings differ from those of Nys et al (2006), further research is needed with larger RH and LH stroke patient groups.…”
Section: Discussionmentioning
confidence: 85%
“…However, in a recent study by our study group (Ruuskanen et al, 2010) it was found that thrombolysis was a significant predictor of earlier discharge to home in patients with moderate/severe RH infarct. Considering those results, it can be hypothesized that our IADL functional outcome measure (FAI) was not sensitive enough to separate the functional outcome of this patient group although in basic ADL functions measured by hospitalization time significant connection to thrombolysis was found.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation